The Paden collection of Arabic materials, Kano, Nigeria - Paden, John N.
Collection includes works of classical Muslim/Arabic literature, especially basic jurisprudential treatises and the better diwans of pre-Islamic Arabic poetry, as well as substantial number of works (especially among the pamphlets) of West African authorship in Hausa/Arabic script.